CROSS-BORDER PROBLEMS AND COOPERATION IN THE FIELD OF ENVIRONMENT IN THE REGULATIONS OF CROATIA, SERBIA, MONTENEGRO AND BOSNIA AND HERZEGOVINA - Todić, Dragoljub C; Todić, Jelena (Glasnik Advokatske komore Vojvodine, 2022)
The paper discusses the normative cooperation frameworks of four Southeast European countries, one of which is the EU member (Croatia), the other two have candidate status (Serbia, Montenegro), and the fourth is in the process of acquiring candidate status (Bosnia and Herzegovina). The introductory part of the paper provides methodological remarks and points to the importance of cross-border problems in the field of environment. The first part of the paper is dedicated to the most important international agreements of a global, (sub)regional and bilateral character, based on which the four states have the obligation (and the right) to cooperate. The second part of the paper presents the most significant provisions of internal law in the field of the environment (basic laws), which refer to cross-border issues and the obligation of states to cooperate. The aim of the paper is to determine the existence and content of the obligation of states to cooperate in the field of environment. Thesis is considered that the obligation of states to cooperate in solving cross-border problems is relatively clearly recognised in the relevant international agreements, and the character of that obligation should be interpreted in the context of the specific obligations and rights of the member states of each international agreement individually. The obligations (and the right) of cooperation are prescribed in the internal regulations of all four states, and the differences could be explained by the specific circumstances that exist in each of them.
Keywords: environment, cross-border problems, principle of cooperation, international agreements, internal regulations, Serbia, Croatia, Montenegro, Bosnia and Herzegovina, EU.